Quality of optimized biogas yields from co-digestion of cattle dung with fresh mass of sunflower leaves, pawpaw and potato peels. Issue 1 (1st January 2018) - Olojede, Moses A.; Ogunkunle, Oyetola; Ahmed, Noor A.
Abstract: Conversion of wastes to energy needs serious attention to boost energy supply and reduce environmental pollution. Biogas yields were obtained from co-digestion of cattle dung with sunflower leaves, pawpaw and potato peels at different compositions in four biogas digesters (A, B, C and D). The substrates were mixed with water in ratio 1:2 and left for a 40-day retention time. Proximate analysis of the substrates, volume and quality of the biogas was determined. Analysis of variance was carried out to show significance of time and temperature over biogas yield. Results revealed that the total volume of biogas and methane content from digester A, B, C and D were 46.64, 45.80, 39.55 and 38.02 m 3, and 71.82%, 53.71%, 66.80% and 52.70%, respectively. Retention time and temperature, at significance level of 0.05, were found to be significant in biogas production. Also, there was high methane contents in the biogas produced.